2018
DOI: 10.1044/2017_lshss-17-0024
|View full text |Cite
|
Sign up to set email alerts
|

Which Preschool Children With Specific Language Impairment Receive Language Intervention?

Abstract: Preschool children with SLI, whose mothers have higher education levels and whose teachers perceive them as having poorer executive functioning, are more likely to receive intervention. Recognizing service delivery biases is critical for improving early provision of intervention for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…This scale is widely used to screen for ADHD, diagnose ADHD, and evaluate treatments of ADHD. The scale includes four forms, a child form (ages 5-10) and an adolescent form (ages [11][12][13][14][15][16][17] for both the home version, which is completed by parents, and the school version, which is completed by teachers. The rating scale items are based on the diagnostic and DSM-5 criteria for ADHD.…”
Section: Consideration Of Additional Standardized Rating Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…This scale is widely used to screen for ADHD, diagnose ADHD, and evaluate treatments of ADHD. The scale includes four forms, a child form (ages 5-10) and an adolescent form (ages [11][12][13][14][15][16][17] for both the home version, which is completed by parents, and the school version, which is completed by teachers. The rating scale items are based on the diagnostic and DSM-5 criteria for ADHD.…”
Section: Consideration Of Additional Standardized Rating Scalesmentioning
confidence: 99%
“…This was particularly troublesome for language impairments given their relatively high prevalence rates, as confirmed by epidemiological study samples, and yet low levels of identification. [13][14][15][16][17] In addition, all five standardized rating scales reviewed included several items in their inventories that could be characterized as either symptomatic of a primary language impairment or representative of a secondary academic consequence (e.g., "Can't talk"; "Doesn't speak clearly"; "Has trouble following directions"; "Difficulty doing homework"). These items typically loaded onto ADHD, Social Problems, or Immaturity subscales across these clinical instruments.…”
mentioning
confidence: 99%
“…In this context, recent research shows promising therapeutic approaches like, for example, grammar training (Smith-Lock, Leitano, Lambert, & Nickels, 2013;Smith-Lock, Leitãno, Lambert, et al, 2013), specific read-aloud techniques (Justice, Logan, & Kaderavek, 2017), or metacognitive and metalinguistic training (Schiff, Nuri Ben-Shushan, & Ben-Artzi, 2017). Furthermore, it was shown that higher education of parents as well as more adequate judgment of executive functions in children by teachers increases the chance that children with SLI receive therapy (Wittke & Spaulding, 2018).…”
Section: Hypothesismentioning
confidence: 99%
“…Receipt of services criteria represents one way of recognizing the contributions of social values to the perceived urgency of addressing different clinical symptoms (see Tomblin, 2006). However, as the results of Morgan et al (2015, 2016), Sciberras et al (2014), Wittke and Spaulding (2018), and Zhang and Tomblin (2000) demonstrate, receipt of services appears to be associated with troublesome inequalities in access. Reproducibility and generalizability of receipt of services as the standard for language impairment status is limited further by the presence of variability in diagnostic and eligibility criteria across clinical settings.…”
mentioning
confidence: 94%
“…Although a prevalence rate of 7%–8% suggests that the average classroom will contain two students with a profile characteristic of SLI, evidence available on the issue indicates that only a minority of children with SLI will receive services to address their limitations and that ascertainment biases within preschool and school-age services are probably systemic. Factors shown to increase the likelihood of receipt of school-based language services after controlling for the severity of children's language impairments include male sex, White race, mothers with postsecondary education, and the presence of concomitant conditions such as speech sound disorder and attention-deficit/hyperactivity disorder (ADHD; Morgan et al, 2015, 2016; Sciberras et al, 2014; Wittke & Spaulding, 2018; Zhang & Tomblin, 2000). Increasing identification rates of children from different backgrounds without concomitant conditions will likely require adoption of school-based screeners targeting language impairments.…”
mentioning
confidence: 99%